2020
DOI: 10.24843/bse.2020.v25.i02.p05
|View full text |Cite
|
Sign up to set email alerts
|

Profitablity and Liquidity on Corporate Value Through Dividend Policy as Intervening Variabel: Empirical Study on Islamic Capital Market

Abstract: The purpose of this study is to examine the effect of profitability and liquidity on dividend policy and firm value. It also examines the role of dividend policy as an intervening variable between profitability and liquidity on firm value. Firm value is measured by Tobin's Q, dividend policy is measured by dividend payout ratio (DPR), profitability is measured by return on assets (ROA) and liquidity is measured by current ratio (CR). The population of this study is companies registered in List of Sharia Securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Research has consistently shown a positive and significant effect of profitability, measured by Return on Assets (ROA), on firm value, indicated by Tobin's Q (Hill & Jones, 1992;Jonnius & Marsudi, 2021;Kurniati et al, 2022;Sutrisno & Panuntun, 2020). However, Return on Equity (ROE) has been found to either negatively impact or have no significant effect on Tobin's Q (Jonnius & Marsudi, 2021;Siti Fatimah, 2022;Nguyen et al, 2022).The role of dividend policy in mediating the relationship between profitability and firm value has also been explored.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Research has consistently shown a positive and significant effect of profitability, measured by Return on Assets (ROA), on firm value, indicated by Tobin's Q (Hill & Jones, 1992;Jonnius & Marsudi, 2021;Kurniati et al, 2022;Sutrisno & Panuntun, 2020). However, Return on Equity (ROE) has been found to either negatively impact or have no significant effect on Tobin's Q (Jonnius & Marsudi, 2021;Siti Fatimah, 2022;Nguyen et al, 2022).The role of dividend policy in mediating the relationship between profitability and firm value has also been explored.…”
Section: Empirical Reviewmentioning
confidence: 99%